Experimental Optimization of R-134a Refrigerant Charge in a Retrofitted Dual Function Refrigeration System for Marine Engineering Applications - Alfanda, Benedicta Dian; Kusuma, George Endri; Maulana, Zulfa; Muninggar, Ratna (International Journal of Marine Engineering Innovation and Research, 2025)
This paper presents an experimental optimization of R-134a refrigerant charge mass in a retrofitted dual function vapor-compression refrigeration system designed to operate in Air-Side (AHU) and Water-Side (Water Chiller) modes. The system was evaluated after retrofit by testing four charge levels—399.5 g (85%), 423.0 g (90%), 446.5 g (95%), and 470.0 g (100%)—under multiple operating conditions: three fan speeds for AHU mode and chilled-water flowrates of 6 8 L/min for chiller mode. Performance was quantified using evaporator capacity Qevap, condenser heat rejection Qcond, compressor electrical power (PcompP_compPcomp), coefficient of performance (COP), and energy efficiency ratio (EER). The results show that the optimal charge is mode- and objective-dependent. In AHU mode, the maximum cooling capacity was obtained at 470 g (100%), reaching Qevap=4.58 kW, while the highest COPactual=3.1234 occurred at 423 g (90%), accompanied by the lowest AHU compressor power Pcomp=1.722 kW). In Water-Side mode, the highest cooling capacity was achieved at 446.5 g (95%), with Qevap=5.141 kW at 6 L/min, whereas the best energy-utilization outcome occurred at 470 g (100%) and 6 L/min, yielding EER = 2.888 with the lowest chiller compressor power Pcomp=1.6524 kW). Overall, the study provides a practical, mode-aware guideline for selecting refrigerant charge in retrofitted dual-function systems for marine engineering applications.